Movimentos sociais e educação : o MST e a construção de uma nova pedagogia - Brito, Flávia de Fatima (2008)
This study is the result of a concern and summarizes a study bibliographic and documentary, whose purpose was to examine how and why the relationship has been Education and Social Movements, taking in particular the development of the process of Implementation and Delivery of Education in the midst of the MST -- Movement of Landless Rural Workers. The choice of the MST was given because we believe that not only by the fact that among the Social Movements he presents himself as something instigating, busy and controversial and even then produced a model "robust" and full of Education, which can be called a "school in Movement ", which in turn draws attention not only by the degree of differentiation to the traditional school, or also for his character but also by teaching it represents in terms of victory and conquest popular, for the conduct of its history, for his maturity and growth . To understand the range and network of new and disturbing facts sought the study of such authors as Gohn (1997), Touraine (1989, 1994) Santos (1994), Caldart (2004), Arroyo (2004) and Freire (1987, 1996, 2000). To the understanding of global climate for the periods from 1980 to the present look authors who develop relevant subjects, as Saints (2003), Anderson (2004), Boron (2004), Oliveira (2004) and Castells (1999). In the analysis take effective object by the School of the MST, for this is a school that has its origin and existence in the midst of the Popular Movement for greater presence in the Brazilian reality.